Bias-Dependent Scanning Tunneling Microscopy Signature of Bridging-Oxygen Vacancies on Rutile TiO(2)(110) - Maddox, Willie B. (ACS Omega, 2018)
[Image: see text] The rutile TiO(2)(110) surface has long-served as a well-characterized, prototypical transition-metal oxide surface used in heterogeneous catalysis and photocatalytic water splitting. Naturally occurring defects on this surface, called bridging-oxygen (BO) vacancies, are important as they determine the overall reactivity of the surface. Herein, we report a bias-dependent, scanning tunneling microscopy (STM) signature of the BO vacancies on TiO(2)(110): for sample bias voltages past a threshold of +3 V, the bright vacancies are flanked on either side (along the oxygen row) by two dark spots approximately shaped like half-moons. The BO vacancies have a bright aspect below the threshold bias also but are not surrounded by half-moon dark depressions. Using generalized gradient approximation calculations with Hubbard correction (GGA + U) for projected density of states (DOS) and simulated STM images, we find that the bias-dependent STM signature originates from (i) local DOS maxima of all BOs (lighter background that occurs above the threshold bias) and (ii) the increased separation between the first and second BO atoms neighboring the vacancy which leads to an apparent dip between these neighboring oxygens. These results offer a new striking example of the STM signature that appears without switching the polarity of the bias. Similar approaches can be employed for seeking distinguishing features on the surfaces of other large band gap semiconductors and insulators.